Variability of arabinoxylan and phytochemicals in refined and whole wheat flour: insights for wheat quality improvement - Gong, Xue; Chen, Tiantian; Tian, Yuanyuan; Zhang, Yan; Ibba, Maria Itria; Wang, Changhai; Zhonghu, He; Chen, Feng; Tian, Wenfei (Elsevier, 2025)
This study explores the variability of arabinoxylans (AX), alkylresorcinols (AR), and ferulic acid (FA) in whole wheat flour (WWF) and refined flour (RF) from 81 representative Chinese wheat varieties, with a focus on implications for wheat quality improvement and breeding. Total AX in RF ranged from 12.60 to 21.55 mg/g, while FA ranged from 90.0 to 156.1 µg/g, demonstrating significant variation across genotypes. ARs were detected only in WWF, reaffirming their role as biomarkers of whole wheat. Strong correlations between AX levels in WWF and RF (r = 0.86, P < 0.001 for WE-AX; r = 0.60, P < 0.001 for TOT-AX) indicate that high-AX wheat varieties can enhance the nutritional quality of both flour types. These findings underscore the genetic potential for developing wheat varieties with improved AX and FA profiles, offering breeders a path to optimize nutritional and functional traits while meeting consumer preferences for refined flour products. These findings offer valuable insights into the genetic and compositional variability of wheat, which could guide breeding efforts aimed at improving wheat quality and meeting diverse consumer needs.